MULTI-CRITERIA SOLAR ENERGY PLANT LOCATION SELECTION USING FUZZY ANP - Demirel, Tufan; Vural, Zeynep (WORLD SCIENTIFIC PUBL CO PTE LTD, 2010)
The aim of the present study is to select the most suitable location for solar energy plant through fuzzy ANP. The problem of selecting location for solar energy plant was considered as a multi-criteria decision making problem. Among the main criteria taken into account in this paper, some are climate, geographical factors, transportation, environmental factors, and costs. This paper also includes some sub-criteria because of the hierarchical structure of the problem, diffuse radiation, average temperature, seismic belt, status of substructure, distance from transformer centers, land use, and installation cost. Then, the problem was solved by using fuzzy ANP method and the best location for the solar energy plant was determined.
Keywords: Multi-criteria decision making; fuzzy; analytic network process; solar energy; plant location; TURKEY; AID; AHP; Computer Science